Alzheimer's disease protease-containing plasma extracellular vesicles transfer to the hippocampus via the choroid plexus - Lee, Jung Hyun; Ostalecki, Christian; Oberstein, Timo; Schierer, Stefan; Zinser, Elisabeth; Eberhardt, Martin; Blume, Katja; Plosnita, Bianca; Stich, Lena; Bruns, Heiko; Coras, Roland; Vera González, Julio; et al. (EBioMedicine, 2022)
Background: Plasma extracellular vesicles (pEV) can harbor a diverse array of factors including active proteases and the amyloid-precursor-protein (APP) cleavage product Aβ, involved in plaque formation in Alzheimer`s diseases (AD). A potential role of such vesicles in AD pathology is unexplored. Methods: In a case-control study of randomly selected patients with AD and other neurological diseases (n = 14), and healthy controls (n = 7), we systematically analyzed the content of pEV, using different assay systems. In addition, we determined their entry path into brain tissue, employing animal (mice) injection experiments with ex vivo generated EV that were similar to AD-pEV, followed by multi antigen analysis (MAA) of brain tissue (n = 4 per condition). The results were compared with an IHC staining of human brain tissue in a small cohort of AD patients (n = 3) and controls with no neurodegenerative diseases (n = 3). Findings: We show that pEV levels are considerably upregulated in AD patients. Besides numerous inflammatory effectors, AD-pEV contained α-, β- and γ-secretases, able to cleave APP in in target cells. In vitro generated EV with similar characteristics as AD-pEV accumulated in the choroid plexus (CP) of injected animals and reached primarily hippocampal neurons. Corroborating findings were made in human brain samples. An inhibitor of hyaluronic-acid-synthetase (HAS) blocked uploading of proteases and Hyaluronan onto EV in vitro and abolished CP targeting in animal injection experiments. Interpretation: We conclude that protease-containing pEV could be part of a communication axis between the periphery and the brain that could be become detrimental depending on pEV concentration and duration of target cell impact.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Alzheimer's disease; APP; Aβ; BACE; Choroid plexus; Hippocampus; Hyaluronan; Hyaluronic acid synthetase; Plasma extracellular vesicles; Secretases

Amyloid-beta levels and cognitive trajectories in non-demented pTau181-positive subjects without amyloidopathy - Oberstein, Timo; Schmidt, Manuel; Florvaag, Anna; Haas, Anna-Lena; Siegmann, Eva-Maria; Olm, Pauline; Utz, Janine; Spitzer, Philipp; Dörfler, Arnd; Lewczuk, Piotr; Kornhuber, Johannes; Maler, Juan Manuel (Brain, 2022)
In a long-term observational study, Oberstein et al. find that the biomarker constellation of increased pTau181, A beta 40 and A beta 42 in CSF is not associated with dementia. Further investigation of this biomarker profile may provide insights into the circumstances under which A beta becomes pathological.
CRIS-Team WoS Importer:2022-09-30

CEREBROSPINAL FLUID BIOMARKERS FOR CEREBRAL AMYLOID ANGIOPATHY - Sembill, Jochen; Lusse, C.; Linnerbauer, Mathias; Sprügel, Maximilian; Mrochen, Anne; Knott, Michael; Hölter, Philip; Engelhorn, Tobias; Schmidt, M.; Dörfler, Arnd; Oberstein, Timo; Maler, Juan Manuel; et al. (INTERNATIONAL JOURNAL OF STROKE, 2022)
CRIS-Team WoS Importer:2022-11-18

Cerebrospinal fluid biomarkers for cerebral amyloid angiopathy - Sembill, Jochen; Lusse, Christoph; Linnerbauer, Mathias; Sprügel, Maximilian; Mrochen, Anne; Knott, Michael; Engelhorn, Tobias; Schmidt, Manuel; Dörfler, Arnd; Oberstein, Timo; Maler, Juan Manuel; Kornhuber, Johannes; et al. (Brain Communications, 2023)
Integrating cerebrospinal fluid-biomarkers into diagnostic workup of patients with sporadic cerebral amyloid angiopathy may support early and correct identification. We aimed to identify and validate clinical- and cerebrospinal fluid-biomarkers for in vivo diagnosis of cerebral amyloid angiopathy. This observational cohort study screened 2795 consecutive patients admitted for cognitive complaints to the academic departments of neurology and psychiatry over a 10-year period (2009–2018). We included 372 patients with available hemosiderin-sensitive MR imaging and cerebrospinal fluid-based neurochemical dementia diagnostics, i.e. Aβ40, Aβ42, t-tau, p-tau. We investigated the association of clinical- and cerebrospinal fluid-biomarkers with the MRI-based diagnosis of cerebral amyloid angiopathy, applying confounder-adjusted modelling, receiver operating characteristic and unsupervised cluster analyses. We identified 67 patients with cerebral amyloid angiopathy, 76 patients with Alzheimer’s disease, 75 patients with mild cognitive impairment due to Alzheimer’s disease, 76 patients with mild cognitive impairment with unlikely Alzheimer’s disease and 78 healthy controls. Patients with cerebral amyloid angiopathy showed a specific cerebrospinal fluid pattern: average concentration of Aß40 [13 792 pg/ml (10 081–18 063)] was decreased compared to all controls (P < 0.05); Aß42 [634 pg/ml (492–834)] was comparable to Alzheimer’s disease and mild cognitive impairment due to Alzheimer’s disease (P = 0.10, P = 0.93) but decreased compared to mild cognitive impairment and healthy controls (both P < 0.001); p-tau [67.3 pg/ml (42.9–91.9)] and t-tau [468 pg/ml (275–698)] were decreased compared to Alzheimer’s disease (P < 0.001, P = 0.001) and mild cognitive impairment due to Alzheimer’s disease (P = 0.001, P = 0.07), but elevated compared to mild cognitive impairment and healthy controls (both P < 0.001). Multivariate modelling validated independent clinical association of cerebral amyloid angiopathy with older age [odds-ratio: 1.06, 95% confidence interval (1.02–1.10), P < 0.01], prior lobar intracerebral haemorrhage [14.00 (2.64–74.19), P < 0.01], prior ischaemic stroke [3.36 (1.58–7.11), P < 0.01], transient focal neurologic episodes (TFNEs) [4.19 (1.06–16.64), P = 0.04] and gait disturbance [2.82 (1.11–7.15), P = 0.03]. For cerebrospinal fluid-biomarkers per 1 pg/ml, both lower Aß40 [0.9999 (0.9998–1.0000), P < 0.01] and lower Aß42 levels [0.9989 (0.9980–0.9998), P = 0.01] provided an independent association with cerebral amyloid angiopathy controlled for all aforementioned clinical confounders. Both amyloid biomarkers showed good discrimination for diagnosis of cerebral amyloid angiopathy among adjusted receiver operating characteristic analyses (area under the receiver operating characteristic curves, Aß40: 0.80 (0.73–0.86), P < 0.001; Aß42: 0.81 (0.75–0.88), P < 0.001). Unsupervised Euclidian clustering of all cerebrospinal fluid-biomarker-profiles resulted in distinct segregation of cerebral amyloid angiopathy patients from all controls. Together, we demonstrate that a distinctive set of cerebrospinal fluid-biomarkers effectively differentiate cerebral amyloid angiopathy patients from patients with Alzheimer’s disease, mild cognitive impairment with or without underlying Alzheimer’s disease, and healthy controls. Integrating our findings into a multiparametric approach may facilitate diagnosing cerebral amyloid angiopathy, and may aid clinical decision-making, but warrants future prospective validation.
CRIS-Team Scopus Importer:2023-07-21
Keywords: biomarker; cerebral amyloid angiopathy; cerebrospinal fluid; dementia; small vessel disease

Cerebrospinal Fluid of Patients With Alzheimer's Disease Contains Increased Percentages of Synaptophysin-Bearing Microvesicles - Utz, Janine; Berner, Judith; Munoz, Luis Enrique; Oberstein, Timo; Kornhuber, Johannes; Herrmann, Martin; Maler, Juan Manuel; Spitzer, Philipp (Frontiers in Aging Neuroscience, 2021)
Introduction In Alzheimer's disease, the severity of symptoms is linked to a loss of synaptic density and the spread of pathologically hyperphosphorylated tau. The established cerebrospinal fluid markers A beta, tau and phospho-tau reflect the histopathological hallmarks of Alzheimer's disease but do not indicate disease progression. Such markers are of special interest, especially for trials of disease modifying drugs. Microvesicles are produced by stressed cells and reflect part of the metabolism of their cells of origin. Therefore, we investigated microvesicles of neuronal origin in cerebrospinal fluid. Materials and Methods We used flow cytometry to analyze microvesicles carrying tau, phospho-tau-Thr181, phospho-tau-Ser202Thr205, synaptophysin, and SNAP-25 in the cerebrospinal fluid of 19 patients with Alzheimer's disease and 15 non-inflammatory neurological disease controls. Results The percentages of synaptophysin-bearing microvesicles were significantly higher in the cerebrospinal fluid of patients with Alzheimer's disease than in the CSF of non-inflammatory neurological disease controls. Tau, phospho-tau-Thr181, phospho-tau-Ser202Thr205, and SNAP-25 did not differ between the groups. The percentages of synaptophysin-bearing vesicles distinguished patients with Alzheimer's disease from the controls (AUC = 0.81). Conclusion The loss of synapses in Alzheimer's disease may be reflected by synaptophysin-bearing microvesicles in the cerebrospinal fluid. Future studies are needed to investigate the possibility of using these MVs as a marker to determine the activity of Alzheimer's disease.
CRIS-Team WoS Importer:2021-07-30

Digit Ratio (2D:4D) Is Not Associated with Alzheimer’s Disease in the Elderly - Siegmann, Eva-Maria; Olm, Pauline; Lenz, Bernd; Mühle, Christiane; Oberstein, Timo; Maler, Juan Manuel; Kornhuber, Johannes (Brain Sciences, 2023)
The development of Alzheimer’s disease (AD) is influenced by sex hormones—estrogens and androgens in particular. However, the impact of prenatal sex hormone exposure is less clear; very few investigations have examined the relationship between the second-to-fourth digit length ratio (2D:4D), a putative proxy for the ratio of prenatal estrogens to androgens, and AD, with inconsistent results among the few that have. Therefore, we aimed to investigate this relationship using methodologically robust metrics. In a 2 (sex) × 4 (group) MANOVA incorporating 108 participants (30 AD patients, 19 patients with tauopathy but no amyloidopathy, 31 clinical and 28 healthy age- and education-matched controls), the effects of sex and group on the dependent variables right and left 2D:4D were examined. We also explored the association between 2D:4D and the severity of AD symptoms assessed via neuropsychological examination. We did not find any significant differences in the right- and left-hand 2D:4D between patients with AD and the other groups; no significant associations between 2D:4D and neuropsychological task performances were found in the dementia groups. The 2D:4D of healthy women was significantly lower than that of depressed women without AD, i.e., clinical controls, but not significantly different from depressed female patients with AD. This investigation does not support the role of 2D:4D in the development or severity of AD in general, but suggests a potential role of 2D:4D for depression in women. Future studies are warranted to clarify whether 2D:4D can distinguish between early- and late-onset depression in women.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Alzheimer’s disease; dementia; digit ratio; fetal development; finger length ratio

DSC Brain Perfusion Using Advanced Deconvolution Models in the Diagnostic Work-Up of Dementia and Mild Cognitive Impairment: A Semiquantitative Comparison with HMPAO-SPECT-Brain Perfusion - Schmidt, Manuel; Engelhorn, Tobias; Lang, Stefan; Lücking, Hannes; Hölter, Philip; Fröhlich, Kilian; Ritt, Philipp; Maler, Juan Manuel; Kuwert, Torsten; Kornhuber, Johannes; Dörfler, Arnd (Journal of Clinical Medicine, 2020)
Background: SPECT (single-photon emission-computed tomography) is used for the detection of hypoperfusion in cognitive impairment and dementia but is not widely available and related to radiation dose exposure. We compared the performance of DSC (dynamic susceptibility contrast) perfusion using semi- and fully adaptive deconvolution models to HMPAO-SPECT (99mTc-hexamethylpropyleneamine oxime-SPECT). Material and Methods: Twenty-seven patients with dementia of different subtypes including frontotemporal dementia (FTD) and mild cognitive impairment (MCI) received a multimodal diagnostic work-up including DSC perfusion at a clinical 3T high-field scanner and HMPAO-SPECT. Nineteen healthy control individuals received DSC perfusion. For calculation of the hemodynamic parameter maps, oscillation-index standard truncated singular value decomposition (oSVD, semi-adaptive) as well as Bayesian parameter estimation (BAY, fully adaptive) were performed. Results: Patients showed decreased cortical perfusion in the left frontal lobe compared to controls (relative cerebral blood volume corrected, rBVc: 0.37 vs. 0.27,p= 0.048, adjusted for age and sex). Performance of rBVc (corrected for T1 effects) was highest compared to SPECT for detection of frontal hypoperfusion (sensitivity 83%, specificity 80% for oSVD and BAY, area under curve (AUC) = 0.833 respectively,p< 0.05) in FTD and MCI. For nonleakage-corrected rBV and for rBF (relative cerebral blood flow), sensitivity of frontal hypoperfusion was above 80% for oSVD and for BAY (rBV: sensitivity 83%, specificity 75%, AUC = 0.908 for oSVD and 0.917 for BAY,p< 0.05 respectively; rBF: sensitivity 83%, specificity 65%, AUC = 0.825,p< 0.05 for oSVD). Conclusion: Advanced deconvolution DSC can reliably detect pathological perfusion alterations in FTD and MCI. Hence, this widely accessible technique has the potential to improve the diagnosis of dementia and MCI as part of an interdisciplinary multimodal imaging work-up. Advances in knowledge: Advanced DSC perfusion has a high potential in the work-up of suspected dementia and correlates with SPECT brain perfusion results in dementia and MCI.
CRIS-Team WoS Importer:2020-07-31

Kidney-transplant patients receiving living- or dead-donor organs have similar psychological outcomes (findings from the PI-KT study) - Müller, Helge H.O.; Lücke, Caroline; Englbrecht, Matthias; Wiesener, Michael; Siller, Teresa; Eckardt, Kai-Uwe; Kornhuber, Johannes; Maler, Juan Manuel (Mental Illness, 2020)
Purpose: Kidney transplantation (KT) is the treatment of choice for end-stage chronic kidney disease (CKD) and is well known to improve the clinical outcome of patients. However, the impact of KT on comorbid psychological symptoms, particularly depression and anxiety, is less clear, and recipients of living-donor (LD) organs may have a different psychological outcome from recipients of dead-donor (DD) organs. Design/methodology/approach: In total, 152 patients were included and analyzed using a cross-sectional design. Of these patients, 25 were pre-KT, 13 were post-KT with a LD transplant and 114 were post-KT with a DD transplant. The patients were tested for a variety of psychometric outcomes using the Hospital Anxiety and Depression Scale, the 12-Item Short Form Health Survey (assessing physical and mental health-related quality of life), the Resilience Scale, the Coping Self-Questionnaire and the Social Support Questionnaire. Findings: The mean age of the patients was 51.25 years and 40 per cent of the patients were female. As expected, the post-KT patients had significantly better scores on the physical component of the Short Form Health Survey than the pre-KT patients, and there were no significant differences between the two post-KT groups. There were no significant differences among the groups in any of the other psychometric outcome parameters tested, including anxiety, depression and the mental component of health-related quality of life. Research limitations/implications: KT and the origin of the donor organ do not appear to have a significant impact on the psychological well-being of transplant patients with CKD. Although the diagnosis and early treatment of psychological symptoms, such as depression and anxiety, remain important for these patients, decisions regarding KT, including the mode of transplantation, should not be fundamentally influenced by concerns about psychological impairments at the population level. Originality/value: CKD is a serious condition involving profound impairment of the physical and psychological well-being of patients. KT is considered the treatment of choice for most of these patients. KT has notable advantages over dialysis with regard to the long-term physical functioning of the renal and cardiovascular system and increases the life expectancy of patients. However, the data on the improvement of psychological impairments after KT are less conclusive.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Coping; Kidney transplantation

PASSED: Brain atrophy in non-demented individuals in a long-term longitudinal study from two independent cohorts - Haas, Anna-Lena; Olm, Pauline; Utz, Janine; Siegmann, Eva-Maria; Spitzer, Philipp; Florvaag, Anna; Schmidt, Manuel; Dörfler, Arnd; Lewczuk, Piotr; Kornhuber, Johannes; Maler, Juan Manuel; Oberstein, Timo (Frontiers in Aging Neuroscience, 2023)
Introduction: Alzheimer’s disease (AD) is indicated by a decrease in amyloid beta 42 (Aβ42) level or the Aβ42/Aβ40 ratio, and by increased levels of Tau with phosphorylated threonine at position 181 (pTau181) in cerebrospinal fluid (CSF) years before the onset of clinical symptoms. However, once only pTau181 is increased, cognitive decline in individuals with subjective or mild cognitive impairment is slowed compared to individuals with AD. Instead of a decrease in Aβ42 levels, an increase in Aβ42 was observed in these individuals, leading to the proposal to refer to them as nondemented subjects with increased pTau-levels and Aβ surge with subtle cognitive deterioration (PASSED). In this study, we determined the longitudinal atrophy rates of AD, PASSED, and Biomarker-negative nondemented individuals of two independent cohorts to determine whether these groups can be distinguished by their longitudinal atrophy patterns or rates. Methods: Depending on their CSF-levels of pTau 181 (T), total Tau (tTau, N), Aβ42 or ratio of Aβ42/Aβ40 (A), 185 non-demented subjects from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) and 62 non-demented subjects from Erlangen AD cohort were assigned to an ATN group (A–T–N–, A–T+N±, A+T–N±and A+T+N±) and underwent T1-weighted structural magnetic resonance imaging (sMRI). Longitudinal grey matter (GM) atrophy patterns were assessed with voxel-based morphometry (VBM) using the cat12 toolbox on spm12 (statistical parametric mapping) of MRI scans from individuals in the ADNI cohort with a mean follow-up of 2 and 5 years, respectively. The annualized atrophy rate for individuals in the Erlangen cohort was determined using region of interest analysis (ROI) in terms of a confirmatory analysis. Results: In the A–T+N± group, VBM did not identify any brain region that showed greater longitudinal atrophy than the A+T+N±, A+T+N± or biomarker negative control group. In contrast, marked longitudinal atrophy in the temporal lobe was evident in the A+T–N± group compared with A+T–N± and biomarker-negative subjects. The ROI in the angular gyrus identified by VBM analysis of the ADNI cohort did not discriminate better than the hippocampal volume and atrophy rate between AD and PASSED in the confirmatory analysis. Discussion: In this study, nondemented subjects with PASSED did not show a unique longitudinal atrophy pattern in comparison to nondemented subjects with AD. The nonsignificant atrophy rate compared with controls suggests that increased pTau181-levels without concomitant amyloidopathy did not indicate a neurodegenerative disorder.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Alzheimer disease/physiopathology*; amyloid beta-peptides/cerebrospinal fluid*; ATN classification; longitudinal studies; magnetic resonance imaging; medial temporal lobe; SNAP; tau proteins/cerebrospinal fluid*

Pharmacological Inhibition of Amyloidogenic APP Processing and Knock-Down of APP in Primary Human Macrophages Impairs the Secretion of Cytokines - Spitzer, Philipp; Walter, Matthias; Göth, Caroline; Oberstein, Timo; Linning, Philipp; Knölker, Hans Joachim; Kornhuber, Johannes; Maler, Juan Manuel (Frontiers in Immunology, 2020)
It has been previously shown that the amyloid precursor protein (APP) support the innate immune defense as an immune receptor. Amyloid β (Aβ) peptides seem to have properties of an antimicrobial peptide and can act as opsonines. In APP-deficient mouse models, a reduced secretion of cytokines has been observed. Still, it is unclear whether this can be attributed to the lack of APP or to the missing secretion of Aβ peptides. We inhibited the secretion of Aβ peptides in primary human monocyte derived macrophages with the γ-secretase inhibitor N-[N-(3,5-Difluorophenacetyl)-L-alanyl]-S-phenylglycine-t-butyl-ester (DAPT) or the β-secretase inhibitor GL-189. Alternatively, we knocked down APP by transfection with siRNA. We measured tumor necrosis factor α (TNFα), interleukin 6 (IL-6) and interleukin (IL-10) by enzyme linked immunosorbent assay (ELISA) and evaluated the phagocytotic activity by flow cytometry. We observed reduced concentrations of TNFα and IL-6 in the media of APPk/d macrophages and after inhibition of the β-, or γ-secretase, especially after additional immunological activation with lipopolysaccharide (LPS). Secretion of IL-10 was increased after pharmacological inhibition of APP processing when the macrophages were not immunologically activated but was decreased during LPS-induced inflammation in APPk/d macrophages. No changes of the phagocytotic activity were observed. We conclude that macrophage APP and Aβ peptides support the initiation of an immune response and are involved in the regulation of TNFα, IL-6, and IL-10 secretion by human monocyte-derived macrophages.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Abeta; Alzheimer; amyloid; amyloid precursor protein; BACE; cytokine; immune system; secretase

Reconceptualization of the Erlangen Score for the Assessment of Dementia Risk: The ERlangen Score - Utz, Janine; Olm, Pauline; Jablonowski, Johannes; Siegmann, Eva-Maria; Spitzer, Philipp; Lewczuk, Piotr; Kornhuber, Johannes; Maler, Juan Manuel; Oberstein, Timo (Journal of Alzheimer's Disease, 2023)
BACKGROUND: The established Erlangen Score (ES) for the interpretation of cerebrospinal fluid (CSF) biomarkers in the diagnostics of Alzheimer's disease (AD) uses markers of amyloidopathy and tauopathy, equally weighted to form an easy-interpretable ordinal scale. However, these biomarkers are not equally predictive for AD. OBJECTIVE: The higher weighting of the Aβ42/Aβ40 ratio, as a reconceptualized ERlangen Score (ERS), was tested for advantages in diagnostic performance. METHODS: Non-demented subjects (N = 154) with a mean follow up of 5 years were assigned to a group ranging from 0 to 4 in ES or ERS. Psychometric trajectories and dementia risk were assessed. RESULTS: The distribution of subjects between ES and ERS among the groups differed considerably, as grouping allocated 32 subjects to ES group 2, but only 2 to ERS group 2. The discriminative accuracy between the ES (AUC 73.2%, 95% CI [64.2, 82.2]) and ERS (AUC 72.0%, 95% CI [63.1, 81.0]) for dementia risk showed no significant difference. Without consideration of the Aβ42/Aβ40 ratio in ES grouping, the optimal cut-off of the ES shifted to ≥2. CONCLUSIONS: The ERS showed advantages over the ES in test interpretation with comparable overall test performance, as fewer cases were allocated to the intermediate risk group. The established cut-off of ≥2 can be maintained for the ERS, whereas it must be adjusted for the ES when determining the Aβ42/Aβ40 ratio.
CRIS-Team Scopus Importer:2023-11-10
Keywords: Alzheimer’s disease; dementia risk; Erlangen Score; longitudinal study; neuropsychological trajectories

The Health Economic Impact of Resource use in Dementia: the Erlanger Dementia Registry (EDR). - Schaller, S. U.; Marinova-Schmidt; Gobin, J.; Luttenberger, Katharina; Richter-Schmidinger, T.; Grässel, Elmar; Maler, Juan Manuel; Kornhuber, Johannes; Kolominsky-Rabas, Peter (Value in Health, 2014)
Dementia patients are in need of more extensive personal care compared to other long-term care users. This Results in a high economic impact of dementia on patients, families and healthcare systems. Due to the increasing prevalence of dementia worldwide, combined with limited healthcare expenditures, a better understanding of resource use in dementia care is needed. Therefore the aim of our study is the assessment of resource use in dementia in the most common setting: home-based care (informal caregivers).<br
EVALuna2:506111

The Role of Cathepsin B in the Degradation of Aβ and in the Production of Aβ Peptides Starting With Ala2 in Cultured Astrocytes - Oberstein, Timo; Utz, Janine; Spitzer, Philipp; Klafki, Hans Wolfgang; Wiltfang, Jens; Lewczuk, Piotr; Kornhuber, Johannes; Maler, Juan Manuel (Frontiers in Molecular Neuroscience, 2021)
Astrocytes may not only be involved in the clearance of Amyloid beta peptides (Aβ) in Alzheimer's disease (AD), but appear to produce N-terminally truncated Aβ (Aβn−x) independently of BACE1, which generates the N-Terminus of Aβ starting with Asp1 (Aβ1−x). A candidate protease for the generation of Aβn−x is cathepsin B (CatB), especially since CatB has also been reported to degrade Aβ, which could explain the opposite roles of astrocytes in AD. In this study, we investigated the influence of CatB inhibitors and the deletion of the gene encoding CatB (CTSB) using CRISPR/Cas9 technology on Aβ2−x and Aβ1−x levels in cell culture supernatants by one- and two-dimensional Urea-SDS-PAGE followed by immunoblot. While the cell-permeant inhibitors E64d and CA-074 Me did not significantly affect the Aβ1−x levels in supernatants of cultured chicken and human astrocytes, they did reduce the Aβ2−x levels. In the glioma-derived cell line H4, the Aβ2−x levels were likewise decreased in supernatants by treatment with the more specific, but cell-impermeant CatB-inhibitor CA-074, by CA-074 Me treatment, and by CTSB gene deletion. Additionally, a more than 2-fold increase in secreted Aβ1−x was observed under the latter two conditions. The CA-074 Me-mediated increase of Aβ1−x, but not the decrease of Aβ2−x, was influenced by concomitant treatment with the vacuolar H+-ATPase inhibitor Bafilomycin A1. This indicated that non-lysosomal CatB mediated the production of Aβ2−x in astrocytes, while the degradation of Aβ1−x seemed to be dependent on lysosomal CatB in H4 cells, but not in primary astrocytes. These findings highlight the importance of considering organelle targeting in drug development to promote Aβ degradation.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Alzheimer's disease; amyloid beta; astrocytes; cathepsin B; lysosomal; N-terminus